History and Methodology of Matan Hadith Criticism Perspective of Salahudin Al-Idlibi - Khusein, Abdul Aziz (Mudir : Jurnal Manajemen Pendidikan, 2023)
Matan criticism is methodologically useful for establishing the authenticity and validity of hadith contents and content. The lack of ambiguity (shadh) and faults ('illah) in the hadith matan is the main rule for establishing its legitimacy. From these two primary concepts, metrics for determining the legitimacy of the hadith matan are created in greater detail, namely: relation to the Qur'an, not contradicting more valid hadiths, not contradicting historical facts, in harmony with rationality, and reflecting prophetic utterances. At first glance, it appears that al- Idlb has no new offers, but historically, he has sought to explore and ensure that criticism of hadith has been carried out since the Companions era and developed in the following years, by including important events and aspects that underpin the emergence of criticism of hadith matan, including manipulative efforts made by certain groups in falsifying hadith. The outcome of research This demonstrates that method critics bro al- Idlb have made an essential contribution to the more extensive history of Matan Hadith critique.